Lignin valorization by bacterial genus Pseudomonas: State-of-the-art review and prospects. (January 2021) - Kumar, Manish; You, Siming; Beiyuan, Jingzi; Luo, Gang; Gupta, Juhi; Kumar, Sunil; Singh, Lal; Zhang, Shicheng; Tsang, Daniel C.W.
Graphical abstract: Highlights: Lignin is a profuse macromolecule and potential feedstock for production of fuels and chemicals. Several thermochemical strategies have been adopted for valorization of lignin. Bacteria conversion is considered as an environmentally friendly approach. Biovalorization of lignin is highly favored by genus Pseudomonas with significant relevance to industrial biotechnology. Abstract: The most prominent aromatic feedstock on Earth is lignin, however, lignin valorization is still an underrated subject. The principal preparatory strategies for lignin valorization are fragmentation and depolymerization which help in the production of fuels and chemicals. Owing to lignin's structural heterogeneity, these strategies result in product generation which requires tedious separation and purification to extract target products. The bacterial genus Pseudomonas has been dominant for its lignin valorization potency, owing to a robust enzymatic machinery that is used to funnel variable lignin derivatives into certain target products such as polyhydroxyalkanotes (PHAs) and cis, cis -muconic acid (MA). In this review, the potential of genus Pseudomonas in lignin valorization is critically reviewed along with the advanced genetic techniques and tools to ease the use of lignin/lignin-model compounds for the synthesis of bioproducts. This review also highlights the research gaps in lignin biovalorization and discuss the challenges and possibilities for future research.